A comparison of foraging‐range sizes, flight distances and foraging habitat preferences in urban and rural House Sparrow (Passer domesticus) populations. (28th May 2022) - Havlíček, Jan; Riegert, Jan; Fuchs, Roman
Abstract : Lack of food for nestlings is a crucial factor influencing population size and dynamics in birds. It is one of the most cited reasons for recent House Sparrow Passer domesticus population declines in cities and rural settlements. However, a detailed comparative study of habitat use by parents delivering food to offspring in different environments is still missing. To obtain the most detailed information on fine‐scale foraging habitat selection, foraging‐range size, flight distance and foraging duration in typical Central European urban and rural environments, we conducted systematic observations of colour‐ringed focal individuals feeding their offspring. We found that urban House Sparrows had larger foraging‐range sizes and longer foraging distances than rural birds. Additionally, some preferred habitats, such as ruderal and woody vegetation, occurred less frequently in the urban area and consequently increased flight distance to key sources of invertebrate prey. In both environments, the most selected habitats – bin storage areas and poultry holdings – offered a stable and rich but probably lower quality 'fast food' source. Birds were willing to fly a longer distance to forage at bin storage areas, tall ruderal vegetation and poultry holdings. Our findings imply that natural food sources in the urban environment are scarce and scattered. Due to the improvement of socio‐economic status associated with better handling of waste products in both urban and rural environments, sprawl of highly urbanized areas and intensification of farming, important foraging habitats have thus decreased. We highlight the importance of maintaining suitable small‐ and medium‐scale farms in rural areas and suggest improvements in the management of green spaces in all types of human settlements that may support House Sparrow populations.